2010
DOI: 10.3109/01612840.2010.520102
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Practices Recorded in Reports of Episodes of Seclusion

Abstract: The purpose of this study is to describe the nursing practices recorded in reports of patient episodes of seclusion, with or without restraints, in a specialized psychiatric facility in Quebec. The reports for all adult patients secluded (n = 4863) in a psychiatric unit between April 1, 2007 and March 31, 2009, were examined. Descriptive analyses were performed. The main reasons for seclusion were agitation, disorganization, and aggressive behaviour. The alternative methods that were attempted included stimulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…An even greater number of patients have been reported to be agitated or disorientated while secluded (92.6%, with or without restraint). In contrast, 77.5% of secluded patients behaved aggressively (Larue et al 2010).…”
Section: Reasons For Seclusion and Restraintmentioning
confidence: 89%
See 2 more Smart Citations
“…An even greater number of patients have been reported to be agitated or disorientated while secluded (92.6%, with or without restraint). In contrast, 77.5% of secluded patients behaved aggressively (Larue et al 2010).…”
Section: Reasons For Seclusion and Restraintmentioning
confidence: 89%
“…Internationally, the use of restrictive measures and the types of measures vary (Noorthoorn et al 2015;Steinert & Lepping 2009;Steinert et al 2010), despite the fact that studies have reported quite similar reasons for seclusion and restraint. These reasons include threats or use of violence against other people or oneself, aggression towards property, attempts to escape from care, inability to care for oneself (Paavola & Tiihonen 2010;Raboch et al 2010), and agitation/disorientation (Kaltiala-Heino et al 2003;Keski-Valkama et al 2009;Larue et al 2010).…”
Section: Reasons For Seclusion and Restraintmentioning
confidence: 99%
See 1 more Smart Citation
“…Coercive measures are usually applied to avert destructive actions against oneself, other patients, or staff. Aggression, especially assault of third persons, disorganization, and agitation, are common catalysts for coercive measures ( 4 7 ). Moreover, HCP often see the therapeutic effects of coercive measures ( 2 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…After seclusion or restraint is over, ventilation and discussion are needed to process all the feelings experienced, to provide psychological and emotional support, to accept the reasons for seclusion and to discuss treatment plans for the future (Mann et al 1993;Kennedy et al 1994;Meehan et al 2000;El-Badri and Mellsop 2008;Ryan and Happell 2009;Keski-Valkama et al 2010a;Larue et al 2010;Needham and Sands 2010;Kontio et al 2012). The importance of being respected as a unique fellow human being cannot be emphasised enough (Välimäki 1998;Chien et al 2005).…”
Section: Patients' Perception Of Seclusion and Restraintmentioning
confidence: 99%